1991
DOI: 10.1007/bf02310573
|View full text |Cite
|
Sign up to set email alerts
|

Complete heart block from mycoplasma pneumoniae infection

Abstract: Complete heart block (CHB) in infants and children is usually congenital. Nonsurgical acquired CHB is rare. Occasionally, transient acquired CHB is seen in association with viral myocarditis. We describe here an unusual case of transient CHB in a 12-year-old boy with endomyocardial biopsy-proven myocarditis and evidence of Mycoplasma pneumoniae infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Exanthemas and gastrointestinal symptoms are quite common [1], whereas Mycoplasma -associated carditis (myo- or pericarditis) is an uncommon complication, occurring in 1–5% of the patients. Since the review by Pönkä [2] published in 1979, we have found 19 additional cases of Mycoplasma- associated carditis in the medical literature [3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16]. During this period, considerable progress regarding diagnosis and treatment has been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Exanthemas and gastrointestinal symptoms are quite common [1], whereas Mycoplasma -associated carditis (myo- or pericarditis) is an uncommon complication, occurring in 1–5% of the patients. Since the review by Pönkä [2] published in 1979, we have found 19 additional cases of Mycoplasma- associated carditis in the medical literature [3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16]. During this period, considerable progress regarding diagnosis and treatment has been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Acquired complete heart block in nonsurgical pediatric patients is rare, most commonly caused by maternal autoimmune antibodies or myocarditis. 2 This is, to our knowledge, the first reported case of calcium deposition secondary to renal disease causing complete AV block in a child with previously normal cardiac conduction and function.…”
Section: Discussionmentioning
confidence: 70%
“…Ponka 10) reported that the mean age was 32 years among the patients with M. pneumoniae associated carditis. Carditis associated with M. pneumoniae may be caused by the following 1,9,11) . Direct in- .…”
Section: Discussionmentioning
confidence: 99%